Adaptive Multi-state Millimeter Wave Cell Selection Scheme for 5G communication - Mothana L Attiah; Azmi Awang Md Isa; Zahriladha Zakaria; Nor Fadzilah Abdullah; Mahamod Ismail; Rosdiadee Nordin (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Millimeter wave bands have been introduced as one of the most promising solutions to alleviate the spectrum secrecy in the upcoming future cellular technology (5G) due the enormous amount of raw bandwidth available in these bands. However, the inherent propagation characteristics of mmWave frequencies could impose new challenges i.e. higher path loss, atmospheric absorption, and rain attenuation which in turn increase the outage probability and hence, degrading the overall system performance. Therefore, in this paper, a novel flexible scheme is proposed namely Adaptive Multi-State MmWave Cell Selection (AMSMC-S) through adopting three classes of mmWave base stations, able to operate at various mmWave carrier frequencies (73, 38 and 28 GHz). Two mmWave cellular Grid-Based cell deployment scenarios have been implemented with two inter-site-distances 200 m and 300 m, corresponding to target area of (2.1 km2) and (2.2 km2). The maximum SINR value at the user equipment (UE) is taken in to consideration to enrich the mobile user experience. Numerical results show an improvement of overall system performance, where the outage probability reduced significantly to zero while maintaining an acceptable performance of the 5G systems with approximately more than 50% of the mobile stations with more than 1Gbps data rate.